REVIEW HISTORIS PENDIDIKAN ISLAM ABAD KE-19 : SEJARAH, TOKOH, PROBLEMA DAN KONTRIBUSI PADA PERADABAN - syafriyon; SA, Saifullah; KAMAL, TAMRIN; Asmaret, Desi; Julhadi (Edusifa: Jurnal Pendidikan Islam, 2025)
This research aims to review the history of Islamic education in the 19th century in the fields of history, problems and contributions to civilization. To take positive values from the progress of Islamic education in the past and take ibrah/lessons from the factors that trigger the decline of Islamic education. Islamic education aims to form perfect humans, carry out religious teachings, create a generation that believes and is devoted to Allah SWT, does good deeds, has noble character, has knowledge and is able to compete with the progress of the times. This research uses a qualitative method, namely in-depth observation of the history of Islamic education in the 19th century, as well as revealing several figures who have succeeded in laying the foundations of Islamic civilization, in building the ummah, as well as the contributions that have been inherited in the world of education, such as: Muhammad Abdh, Rasyid Ridah, Jamaludin Al Afgani, Fathi al-Fawzan, as well as Indonesian national figures such as Syekh Ahmad Kahtib Al Minangkabawi, KH. Ahmad Dahlan, Hasyim al-'Asy'ari, Rahma El Yunusiyah and others. They were figures who contributed greatly to building Islamic civilization. Islamic education figures contributed to the development of Islam so that it was able to reach the peak of Islamic glory during the Abbasid dynasty as evidenced by the birth of famous Islamic figures such as Al Farabi, Ibnu Sina, Ibn Tufail and left a valuable legacy in science. The contribution of written works from Islamic figures becomes gold work and is very valuable as a reference in the world of education